Argosfestival 2003. - André, Yael; Feder, Elena; Iles, Chrissie; de Bruyn, Eric; Stevenheydens, Ive; Hegarty, Paul; Muller, Nat; Royoux, Jean-Christoph; Blüminger, Christa (Brussel : Argos Editions, 2003)
Abendroth, Manuel ; Albers, Beatrijs ; Van Allemeersch, Frederik ; André, Marie ; André, Yaël ; Atrux-Tallau, Laurette ; Aubier, Stéphane ; Augustijnen, Sven ; Avoort, Boris Van der ; Baes, Pascal ; Balcaen, Bert ; Barry, Orla ; De Bemels, Antonin ; De Bièvre, Guy ; Bismuth, Pierre ; Blondeel, Maria ; Bochet, Milena ; De Boe, Rik ; Bohnenberger, Stefan ; Boon, Elke ; Boutique Vizique ; Brand, Jens ; Breës, Gwenaël ; Bucquoy, Jan ; Building Transmissions ; Van den Bulcke, Kora ; Busch, Harald ; Butt, Katja ; Callebert, Maarten ; Cardell, Amanda ; Case, Charley ; Casinière, Joëlle de la ; Catrysse, Wim ; Cattelain, Claude ; Charlier, Jacques ; Claes, Axel ; De Clercq, Anouk ; Code 31 ; Colinet, André ; Convert, Jean-Philippe ; Coulibeuf, Pierre ; Crabeels, Cel ; De Cupere, Peter ; Curlet, François ; D'Hondt, Lieve ; d'O, Honoré ; Debackere, Boris ; Debauche, Jennifer ; Decock, Jérome ; Dekyndt, Edith ; Delacourt, Kris ; Dementieva, Alexandra ; Denicolai, Simona ; Deprez, Dany ; Destoop, Alexis ; Dialogist-Kantor ; Dierckx, Ben ; Dockx, Nico ; Downsbrough, Peter ; Duclaux, Lise ; Dufranne, Nicolas ; Durand, Philippe ; Durt-Morimoto, Ali ; Experimental Intermedia ; Florizoone, Jan ; Foam ; François, Michel ; Gansomaeda ; Garcia, Dora ; Garrec, Ryan Le ; Gate4 ; Gigounon, Bernard ; Giloux, Pierre-Jean ; Graux, Guillaume ; De Gruyter, Jos ; Hachet, Vincent ; Hamaide, Stéphanie ; Harvey, Aureia ; Heiremans, Ronny ; Heremans, Pieter ; Horiguchi, Kazunari ; Huybrechts, Jo ; Iikawa, Takehiro ; Ikeda, Yoshito ; Jakar, Michel ; Janssens de Bisthoven, Sylvie ; Janssens, Ann Veronica ; Kaltenegger, Iris ; Kapotski ; Van Kerckhoven, Anne-Mie ; Kolleman, Robin ; Kollischan, Eva ; Konrad, Aglaia ; Krajinovic, Jasna ; Kuntz, Raphaël ; LAB[au] ; etc.
Argosfestival 2003, Brussel, 17 - 25/10/2003
boek